Análise operacional do desempenho de sistemas de geração fotovoltaica utilizando inversores do tipo String e microinversor - Silva, Daniel Santos (Universidade Federal do Tocantins, 2021)
Photovoltaic distributed generation is one of the most promising renewable sources today. The state of Tocantins stands out for its favorable conditions due to its location close to the equator, causing one of the largest solar radiation in Brazil. The study of photovoltaic inverters is essential in the search for the best use of the photovoltaic modules, greater efficiency and consequence, for promoting the best possible use of the set of knowledge that make up the system and the climatic conditions. This work explores the concepts of solar energy, photovoltaic generation potential connected to the grid in Brazil and Tocantins, performance factors and external factors that can affect generation. From this, it presents a case study of analysis and comparison between six systems with two types of inverter technology, the string type inverter and the microinverter, through the data collection of systems in operation in the city of Palmas-TO. With this presentation, it will be possible to learn more about each technology and its characteristics in the region.